Thoracic epidural arteriovenous malformation causing rapidly progressive myelopathy and mimicking an acute transverse myelitis: A case report - Hao Yuan; Yu Pi; Hong‐Su Zhou; Chong Wang; Wei Liu; Yong‐Min Niu; Yang Lan; Dong Chen; Shi‐Ran Liu; Shun‐Wu Xiao (Ibrain, 2022)
Abstract Clinical symptoms of spinal arteriovenous malformations (AVMs) combined with acute spontaneous hemorrhage lack specificity, which leads to misdiagnosis and delays treatment. The current study aimed to analyze the causes of misdiagnosis and review the key points of diagnosis and treatment. We presented an extremely rare case of a 25‐year‐old man whose clinical characteristics mimicked acute transverse myelitis, suffering from rapidly and repeatedly progressive myelopathy with a mass. The pathological diagnosis of the mass was AVM; symptom‐based surgical treatment with posterior decompression and the removal of epidural AVMs during the postoperative 12‐month follow‐up period were performed. The manual muscle testing grade score of the proximal and distal muscles in both lower limbs improved from 1 to 5, and the American Spinal Injury Association motor and sensation grade score improved from B to E. In the case of sudden or progressive spinal cord injury of unknown cause and acute spinal cord dysfunction, there might be a misdiagnosis. The key to a differential diagnosis is to take into account AVMs, and spontaneous hemorrhages and hematomas should also be suspected. Angiography and magnetic resonance imaging are very important for the diagnosis of AVM, and we hope to enhance clinicians' understanding of and vigilance for such diseases.